SARS-CoV-2 infection causes prolonged cardiomyocyte swelling and inhibition of HIF1α translocation in an animal model COVID-19 - Daems, Margo; Liesenborghs, Laurens; Boudewijns, Robbert; Simmonds, Steven J.; Kraisin, Sirima; Van Wauwe, Jore; Cuijpers, Ilona; Raman, Jana; Geuens, Nadèche; Buyten, Tina Van; Lox, Marleen; Verhamme, Peter; et al. (Frontiers in Cardiovascular Medicine, 2022)
Recovered COVID-19 patients often display cardiac dysfunction, even after a mild infection. Most current histological results come from patients that are hospitalized and therefore represent more severe outcomes than most COVID-19 patients face. To overcome this limitation, we investigated the cardiac effects of SARS-CoV-2 infection in a hamster model. SARS-CoV-2 infected hamsters developed diastolic dysfunction after recovering from COVID-19. Histologically, increased cardiomyocyte size was present at the peak of viral load and remained at all time points investigated. As this increase is too rapid for hypertrophic remodelling, we found instead that the heart was oedemic. Moreover, cardiomyocyte swelling is associated with the presence of ischemia. Fibrin-rich microthrombi and pericyte loss were observed at the peak of viral load, resulting in increased HIF1α in cardiomyocytes. Surprisingly, SARS-CoV-2 infection inhibited the translocation of HIF1α to the nucleus both in hamster hearts, in cultured cardiomyocytes, as well as in an epithelial cell line. We propose that the observed diastolic dysfunction is the consequence of cardiac oedema, downstream of microvascular cardiac ischemia. Additionally, our data suggest that inhibition of HIF1α translocation could contribute to an exaggerated response upon SARS-CoV-2 infection.